Hepatocellular liver injury in hospitalized patients affected by COVID-19: Presence of different risk factors at different time points. Issue 5 (May 2022) - Leo, M.; Galante, A.; Pagnamenta, A.; Ruinelli, L.; Ponziani, F.R.; Gasbarrini, A.; De Gottardi, A.
Abstract: Background: Prevalence and clinical impact of increased liver function tests in patients affected by Coronavirus disease 2019 (COVID-19) is controversial. Aims: This observational study evaluates the prevalence of transaminases elevation in hospitalized patients affected by COVID-19 and investigates the presence of factors associated with hepatocellular injury and with mortality. Methods: Data of 292 adult patients with confirmed COVID-19 admitted to the Ente Ospedaliero Cantonale (Switzerland) were retrospectively analyzed. Results: Transaminases were increased in about one-third of patients on hospital admission and two-thirds of patients during the hospital stay. On hospital admission, transaminases were more commonly elevated in younger patients, who also reported elevated C reactive protein and a higher degree of respiratory failure. Independent factors associated with abnormal transaminases during hospitalization were drugs, in particular paracetamol (OR=2.67; 95% CI=1.38–5.18; p = 0.004) and remdesivir (OR=5.16; 95% CI=1.10–24.26; p = 0.04). Mortality was independently associated to age (OR = 1.09; 95% CI=1.05–1.13; p <0.001), admission to intensive care unit (OR=5.22; 95% CI=2.28–11.90; p <0.001) and alkaline phosphatase peak (OR=1.01; 95% CI=1.00- 1.01; p = 0.01). Conclusions: On hospital admission, factors associated with liver damage were linked to demographic and clinical characteristics (age, inflammation and hypoxia) while, during hospitalization, drug treatment was related to development and progression of hepatocellular damage. Mortality was associated with alkaline phosphate peak value.